The Analysis Of Highest And Best Use In State Property (Bmn): Optimization Case Study In Kediri Regency - Tama, Pradina Mukti; Amirya, mirna (The International Journal of Accounting and Business Society, 2025)
Purpose: This study aims to develop and apply an integrated Highest and Best Use (HBU) framework that incorporates environmental regulations, specifically river boundary requirements, to optimize the utilization of potentially idle State Property (BMN) in Indonesia, thereby balancing economic returns with regulatory compliance. Design/methodology/approach: The research employed a case-study approach in Kediri Regency, analyzing a vacant government land parcel. The methodology involved comprehensive stakeholder consultations (with asset managers, property officers, appraisers, and community representatives) and an enhanced HBU evaluation that assessed alternative land uses across four criteria: legal, physical, financial, and productivity maximum. Findings: Two primary alternatives were identified: warehouse and sugarcane plantation. A comparative financial analysis demonstrates that the warehouse alternative achieves superior economic performance, with an NPV of Rp 18.5 billion, an IRR of 16.37%, and an annual net income of Rp 4.6 billion. This substantially exceeds the returns from the sugarcane plantation (Rp 57 million annually). Furthermore, the warehouse option demonstrates optimal land productivity, strategic use of location, and compliance with spatial planning regulations. Practical implications: This research provides government asset managers with a practical, evidence-based framework for optimizing idle assets. The framework ensures adherence to environmental regulatory compliance while simultaneously maximizing economic value. Originality/value: The methodology provides a replicable template for optimizing state property across diverse geographic and regulatory contexts. It contributes to improved public asset management practices and enhanced government financial performance within the Indonesian context.